Avaliação da assistência à saúde do idoso : um estudo de caso no CEASI - NATAL/RN - Silva, Eliude Lúcia Abreu da (2009)
The evaluation of health care of the elderly is becoming a pressing need in the face of population explosion in this population segment of the world. In the Brazilian case, projections indicate that within twenty years it will be the sixth most-aged country in the word. The object of study of this research is to analyze the evaluation of the programs, projects, services and activities of the health care of the elderly from the indicators of accessibility, quality and effectiveness. This research aims to establish whether the programs , projects, services and activities of the health care of the elderly produce positive impacts in these users from the perspective of quality of life. For both, the research sought to evaluate the health car of the elderly, developed by Specialized Center for Health Care of the Elderly (CEASI), In The City of Natal/RN. In methodological terms, this process is investigative typified as a search field of character with the adoption of evaluative tools and techniques quali-quantitative using the chip cadastral institutional , the questionnaire with the professionals and semi-structured interviews with 40 (forty) elderly, users CEASI. The data collection occurred between the years of 2006 to 2007. The collected data were analyzed using descriptive statistics of reading and analysis of content categorization by topic. The results showed that 100% of the elderly interviewed seeking programs and curative health services, 90% are carriers of chronic diseases, 87,5% have problems of access to services of CEASI, both to personal, especially difficulty of mobility and financial and institutional order, especially the bureaucracy and geographic location of the centre. . In inconclusive terms, it shows that although the proposed program of work of CEASI inset itself in the perspective of the rights of senior citizens, the achievement of universality and accessibility is far from effective. It was found that despite the existence of social legislation to guarantee the rights of the elderly, there are significant parcels of the group who are excluded, especially their rights to health care. Evidence itself as elements constraints in this table: the lack of clarification and ignorance Aging of his health/disease , as well as the existence of structural determinants that hamper access, quality and effectiveness of health care.